Aplikasi Tenaga Surya sebagai Sumber Energi Alternatif - Nur - Hayati (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2021)
This community service program aims to utilize solar power as a source of electrical energy to replace the PLN electricity source at Bopongan RT 04 Padukuhan Kauman, Tamanan, Banguntapan, Bantul. The method of implementing this abdimas begins with data collection of residents 'houses that have not yet been supplied with electricity from PLN, then socialization is carried out about the theory of solar panels to residents and ends with the installation of solar panels in residents' homes. The results of the Community Service were quite satisfying, namely residents who had not yet received PLN electricity were able to enjoy lighting with alternative energy sources.